DOŚWIADCZENIE PRZESTRZENI W PAMIĘCI O HOLOCAUŚCIE - Podbielska, Alicja (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
This paper analyzes different experiences of space by which memory of Holocaust could be passed on. The Memorial for the murdered Jews of Europe in Berlin gives visitors the feeling of insecurity and overwhelms them with monumentality. For that reason it is criticized as reflecting the other side of German memory: The Third Reich’s megalomania and dream about power. The Hamburger memorial against fascism designed in 1986 by conceptual artists Jochen and Esther Gerz offers quite an opposite experience of space. A twelve-meter-high pillar has been established for visitors to sign on it. Once the area was covered by signature it was lowered into the ground till it completely disappeared. The intention of the artists was to put memory not into the monument but into people. Pozdrowienia z Alej Jerozolimskich (Greetings from the Jerusalem Avenue, 2002) by Joanna Rajkowska – a fifteen-meter tall artificial palm tree installed in the centre of Warsaw – is an attempt to infuse with Israel's scenery a Warsaw's street whose name and history sends the observer to the history of the Jews in Poland. In another work called Dotleniacz (Oxygenator, 2007) Rajkowska created an artificial lake with oxygen concentrators, gold fish, flowers and banks. Again, the installation was placed in a very meaningful place – Grzybowski Square – which is strongly connected with Jewish life in Poland as well as Polish anti-Semitism. The synagogue in Poznan was transformed during the Nazi occupation into a swimming pool which it has remained until the present day. This fact ( just like the building) seems to be invisible for most citizens. In 2003 Rafał Jakubowicz changed the fact by projecting a Hebrew inscription הייחש-תכירב (swimming pool) on the façade of the former synagogue. In Berek (The Game of Tag, 1999) by Artur Żmijewski a group of naked men and women of various age play tag. The artist filmed them in two rooms: in a symbolically neutral space and in a gas chamber of a former Nazi death camp. The film is an attempt at breaking the spell of this horrifying and paralysing space.
Experience of space in the memory of Holocaust
Keywords: pomnik; monument; pamięć; memory; przestrzeń; space; anty-pomnik; anti-monument; Holocaust